Transformational Da'wah Leadership Model of Persatuan Islam (Persis) Organization in Facing Global Challenges - Zaenudin, Jeje; Fauzan, Pepen Irpan; Rustandi, Ridwan (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2024)
This study analyzes the transformational da'wah leadership model of Persatuan Islam during the 2022-2027 period when the organization entered its first century. Using the constructivism paradigm and a qualitative approach through the case study method, this study investigates the mainstreaming of Persis da'wah in terms of discourse, movement, and activity, especially those reflected in the leadership vision and jihad program of the Central Leadership for the 2022-2024 period. Data was collected through in-depth interviews with Persis leaders, participatory observation, and document analysis, which were then analyzed using thematic analysis techniques. The study results show that transforming the Persis paradigm from